A Scientometric and Bibliometric Analysis for Actinomycetes Research - Current Status and Future Trends - Syahri, Syahri; Somantri, Renny Utami (Jurnal Perlindungan Tanaman Indonesia, 2022)
Actinomycetes are Gram-positive filamentous bacteria used as biocontrol agents against pathogens. Currently, little research on actinomycetes has been published in Indonesia. The study provides issues related to the most relevant keywords in actinomycetes, the most productive authors and countries on actinomycetes research, current research on actinomycetes, and future topics in actinomycetes research. This paper aims to understand the current status and trend of research on actinomycetes in biological control, especially their acts as biocontrol agents. We used VOSviewer and CiteSpace software to perform a scientometric and bibliometric analysis. Out of 452 Scopus publications published between 1971 and 2022. Research on actinomycetes has increased rapidly since 2000, leading to an exponential trend. The result shows that >50% of papers focus on Agricultural and Biological Sciences and indicate that actinomycetes are mainly applied as biocontrol agents. China is the most documented and powerful country, followed by the United States and Iran. In contrast, Indonesia ranks 19th in the world with nine published papers. Scientometric analysis shows Shahidi Bonjar nominated as the strongest citation burst author (4.01). Their topic is mainly on the biological control of pathogens by Actinomycetes, especially Streptomyces sp., while fungi are a dominant pathogen. These findings are related to bibliometric analysis, showing Streptomyces spp. and fungi are two primary keywords in the Scopus database, found on 183 and 139 documents. We found actinomycete research focuses on their ability to manage plant diseases naturally. In the future, we predict actinobacterial research is still essential to biological control, particularly those involving Streptomyces species. Also, several important topics are associated with their activities in controlling pests (nematode), postharvest disease, and growth promoter ability.